Subcutaneous tissue reaction to castor oil bean and calcium hydroxide in rats - Samira Esteves Afonso Camargo; Sigmar de Mello Rode; Renata Falchete do Prado; Yasmin Rodarte Carvalho; Carlos Henrique Ribeiro Camargo (University of São Paulo, 2010)
Castor oil bean cement (COB) is a new material that has been used as an endodontic sealer, and is a candidate material for direct pulp capping. OBJECTIVE: The purpose of this study was to evaluate the biocompatibility of a new formulation of COB compared to calcium hydroxide cement (CH) and a control group without any material, in the subcutaneous tissue of rats. MATERIAL AND METHODS: The materials were prepared, packed into polyethylene tubes, and implanted in the rat dorsal subcutaneous tissue. Animals were sacrificed at the 7th and 50th days after implantation. A quantitative analysis of inflammatory cells was performed and data were subjected to ANOVA and Tukey's tests at 5% significance level. RESULTS: Comparing the mean number of inflammatory cells between the two experimental groups (COB and CH) and the control group, statistically significant difference (p=0.0001) was observed at 7 and 50 days. There were no significant differences (p=0.111) between tissue reaction to CH (382 inflammatory cells) and COB (330 inflammatory cells) after 7 days. After 50 days, significantly more inflammatory cells (p=0.02) were observed in the CH group (404 inflammatory cells) than in the COB group (177 inflammatory cells). CONCLUSIONS: These results demonstrate that the COB cement induces less inflammatory response within long periods.